Trauma, the Holy Spirit, and Spiritual Formation: Facilitating Recovery in the Mind, Spirit, and Body - Wang, David C. (Journal of spiritual formation & soul care, 2024)
The impact of trauma is pervasive, multi-faceted, and longstanding, impacting the mind, body, and spirit. Trauma can unfold with a cascading effect throughout every stage of life, leaving its mark on brain development, stunting social, emotional, and cognitive functioning, promoting risky health behavior, and increasing vulnerability to chronic disease, and ultimately leading to early death. Consistent with this reality, recovery from trauma is a gradual, iterative journey of reshaping or reparenting the brain over time. Trauma is also endemic to the Christian faith and to Christian communities, with its signs and effects persisting after divine and/or conventional healing. This was also the case with Christ, who bore scars and memories of his crucifixion in his post-resurrection body. The substantial though partial and imperfect nature of healing from trauma reflects the dynamics of the already-but-not-yet Kingdom of God in which the world remains in darkness and God’s Kingdom remains incomplete. This reality coexists, however, alongside genuine signs of the eschatological Kingdom that is dawning and an invitation towards Christian community and accompaniment—perhaps the greatest gift of the Holy Spirit for healing and recovery. This paper is part of a special issue on the topic of the Holy Spirit and the healing of the body.